Landscape as a Model of Architecture: A Contemporary Imitation - Quesada-García, Santiago (Arte, Individuo y Sociedad, 2021)
The act of designing architecture is based on the use of various models chosen as referents. Such models may come from architecture itself or from the arts like sculpture, painting, music, literature, and so forth. They usually provide the components for architectural design. This stance leads to the notion of architectural design as the construction of a new order derived from elements, examples, or prototypes verified in time by virtue of experience. Thus, the praxis of the design process is mainly referred to as a conscious imitation of models. The thesis of this work is that landscape constitutes one of these models. Landscape should be considered a contemporary model for architectural imitation because it is a concept that reveals a dynamic reality oriented towards the future. The values of landscape produce a wish to emulate it, to assimilate it. In a renewed object–subject relationship, landscape proposes itself as a paramount issue for architectural design. This paper contextualizes and explains what comprises such renewed mimesis and why landscape is a subject that provokes a desire for active emulation in contemporary architecture.